Uji Aktivitas Antibakteri Ekstrak Etanol 95% Daun Tekelan (Chromolaena odorata. L) terhadap Bakteri Shigella disenteriae - Fitrianingsih, Ade Irma; Kurniawan, Rauhul Akbar; Putri, Ulfa Ersa (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Indonesia is a tropical country, so the prevalence of infectious diseases caused by bacteria is still high. On the other hand, the intense use of antibacterials in Indonesia causes a tendency to develop bacterial resistance to existing antibacterial drugs. One of the bacterial species that causes infection is Shigella dysenteriae. Chromolaena odorata L is a plant that can be used as an antibacterial. This study aims to determine whether the ethanolic extract of Chromolaena odorata L has antibacterial activity against Shigella dysenteriae bacteria. Chromolaena odorata L ethanol extract was prepared by maceration method using 95% ethanol extractor solution. The research was conducted by well diffusion method. The results showed the presence of inhibition in bacteria indicated by the average results of measurements of each concentration, namely: 25% (23.6 mm), 50% (25.5 mm), 75% (27.6 mm) and 100% (29 ,3mm). From the results of the study, it can be concluded that the Chromolaena odorata L have antibacterial activity against the bacteria Shigella dysenteriae.